2012
DOI: 10.1021/ie201868z
|View full text |Cite
|
Sign up to set email alerts
|

Particle Number and Size Emissions from a Small Displacement Automotive Diesel Engine: Bioderived vs Conventional Fossil Fuels

Abstract: Experimental work has been carried out on a small displacement Euro 5 automotive diesel engine fueled alternatively with ultralow sulfur diesel (ULSD) and with two blends (30% vol) of ULSD, with two different fatty acid methyl esters (FAME) obtained from rapeseed methyl ester (RME) and jatropha methyl ester (JME). The engine-out particulate matter (PM) emissions have been characterized in terms of number and mass size distributions; measurements were performed under different engine operating conditions that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…For example, Wang et al [14] have shown that adding oxygenated hydrocarbons (HC) to diesel can lead to an increase in HC, CO, NOx and NO2 emissions, but at the same time to a decrease in the number of particulate matters. On the other hand, the use of fatty acid methyl esters leads to a decrease in the size of particles formed, while their number is not significantly affected [15].…”
Section: State Of the Artmentioning
confidence: 95%
“…For example, Wang et al [14] have shown that adding oxygenated hydrocarbons (HC) to diesel can lead to an increase in HC, CO, NOx and NO2 emissions, but at the same time to a decrease in the number of particulate matters. On the other hand, the use of fatty acid methyl esters leads to a decrease in the size of particles formed, while their number is not significantly affected [15].…”
Section: State Of the Artmentioning
confidence: 95%
“…The adverse effects of vehicular emissions, especially particulate matter emissions on health and environment have triggered research interests in fuel formulations (Chen et al, 2012b;Giakoumis et al, 2012;Millo et al, 2012;Chen et al, 2015;Amara et al, 2016), engine calibration and designs (Chen et al, 2012a;Lee and Jeong, 2012;Tan et al, 2014;Chen et al, 2017), and effective after treatment technologies (Mamakos et al, 2013b;Lee et al, 2015) to reduce ultrafine particle emissions. Increasingly stringent regulations such as Euro 5/6 legislation, which specifies a non-volatile particle number emission limit of 6 × 10 11 particles km -1 to complement the mass-based limit for particulate emissions from light-duty diesel vehicles, have been proposed Otsuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, both (1) and (2) present the same variation relation between (dΔ /d ) initial and the pore size distribution range (3 ). Reducing 3 would reduce the value of the (dΔ /d ) initial and eventually lead to low final DPF pressure drop.…”
Section: The Relationship Between the Pore Structure And Initialmentioning
confidence: 90%
“…From (1), the values of (dΔ /d ) initial are directly proportional to the viscosity , 2 , 3 , and and inversely proportional to 3 . The values of the parameter DB defined by (1) are calculated using the above parameters, and the relationship between (dΔ /d ) initial and DB is presented in Figure 8.…”
Section: The Relationship Between the Pore Structure And Initialmentioning
confidence: 99%
See 1 more Smart Citation